Coated lithium-rich metal oxide material and preparation method thereof, method for determining coating layer in coated lithium-rich metal oxide material, positive pole piece, battery and electric device
Patent Information
- Application Number
- CN202280096509.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-07
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-11-07
AI Technical Summary
Lithium in lithium-rich metal oxide materials is easy to dissolve, causing side reactions to generate alkaline by-products, affecting the migration of lithium ions, reducing the charging capacity of the battery and increasing the resistance.
The coating type lithium-rich metal oxide material is used to form a coating layer of carbon, silicon oxide and metal oxide through plasma enhanced chemical vapor deposition method to reduce the dissolution of lithium ions and improve the integrity and compactness of the coating layer. , reduce the battery resistance.
It increases the migration rate of lithium ions, increases the charging capacity of the battery, reduces the resistance of the material, and enhances the stability and compactness of the coating layer.
Smart Images

Figure CN119256405A_ABST
Abstract
Description
Coated lithium-rich metal oxide material and preparation method, method for determining coating layer in coated lithium-rich metal oxide material, positive electrode sheet, battery and electrical device Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a coated lithium-rich metal oxide material, a method for preparing the coated lithium-rich metal oxide material, a method for measuring a coating layer in the coated lithium-rich metal oxide material, a positive electrode sheet, a battery, and an electrical device. Background Art
[0002] In recent years, the application of secondary batteries has become increasingly widespread. They are widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. As secondary batteries have achieved great development, higher requirements have been placed on their energy density, cycle performance, and safety performance.
[0003] The lithium content in lithium-rich metal oxide materials is high, and they are easily dissolved into the external environment and react with carbon dioxide and / or water as side reactions, generating highly alkaline, gel-like byproducts on the surface of the material, which affects the migration of lithium ions, reduces the battery's charging capacity, and increases the material's resistance.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a coated lithium-rich metal oxide material, a method for preparing the coated lithium-rich metal oxide material, a method for measuring the coating layer in the coated lithium-rich metal oxide material, a positive electrode plate, a battery and an electrical device. The coated lithium-rich metal oxide material of the present application has a coating layer with high integrity and density, which can reduce the dissolution of lithium in the lithium-rich metal oxide core to the outside to cause side reactions, thereby increasing the capacity of the battery, reducing the material resistance, and increasing the migration rate of lithium ions; the method for measuring the coating layer in the coated lithium-rich metal oxide material of the present application can accurately and quickly measure the integrity and density of the coating layer, and is simple to operate.
[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a coated lithium-rich metal oxide material, comprising a core and a coating layer coating the core;
[0007] The core contains Li a MO y ; Wherein, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb and Cr, 2≤a≤6, 2≤y≤4;
[0008] The coating layer comprises one or more of carbon, silicon oxide, and metal oxide;
[0009] The weight growth rate of the coated lithium-rich metal oxide material after standing for 144 to 192 hours in an environment of 25° C. and 40% relative humidity is w, w<0.8%;
[0010] Optionally, w≤0.5%.
[0011] Therefore, the coated lithium-rich metal oxide material of the present application has a coating layer with high integrity and density, which reduces the dissolution of free lithium in the lithium-rich metal oxide core, thereby reducing the side reactions of the dissolved free lithium with external substances, improving the charging capacity of the battery, increasing the migration rate of lithium ions, and reducing the resistance of the material.
[0012] A second aspect of the present application provides a coated lithium-rich metal oxide material, comprising a core and a coating layer coating the core;
[0013] The core contains Li a MO y ; Wherein, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb and Cr, 2≤a≤6, 2≤y≤4;
[0014] The coating layer comprises one or more of carbon, silicon oxide, and metal oxide;
[0015] Moreover, the d value of the coated lithium-rich metal oxide material satisfies:
[0016] When 2≤a<3, d≤500ppm;
[0017] When 3≤a<4, d≤1000ppm;
[0018] When 4≤a≤6, d≤1500ppm;
[0019] The d value of the coated lithium-rich metal oxide material is determined by the following steps:
[0020] The coated lithium-rich metal oxide material is mixed with a solvent in a mass ratio of 1:50 to 1:1, wherein the solvent consists of water and ethanol, the mass content of water in the solvent is b, and b satisfies:
[0021] When 2≤a<3, b=100%-a×10%;
[0022] When 3≤a<4, b=100%-a×20%;
[0023] When 4≤a≤6, b=0;
[0024] The liquid phase in the obtained mixture is separated and subjected to potentiometric titration to calculate the free lithium content dissolved in the coated lithium-rich metal oxide material, which is the d value of the coated lithium-rich metal oxide material.
[0025] Therefore, on the basis of the first aspect, the integrity and density of the coating layer in the coated lithium-rich metal oxide material of the present application are further improved, the dissolution of free lithium in the lithium-rich metal oxide core is further reduced, and the side reaction of the dissolved free lithium with the outside world is further reduced, thereby further improving the charging capacity of the battery, further improving the migration rate of lithium ions, and further reducing the resistance of the coated lithium-rich metal oxide material.
[0026] In any embodiment, M includes one or more elements of Ni, Co, Fe, Mn, Cu, V, and Nb, and optionally includes one or more elements of Ni, Co, Fe, Cu, and Nb.
[0027] In any embodiment, the core includes one or more of Li2NiO2, Li2CuO2, Li2MnO3, Li3VO4, Li3NbO4, Li5FeO4 and Li6CoO4, and optionally includes one or more of Li2NiO2, Li2CuO2, Li3NbO4, Li5FeO4 and Li6CoO4.
[0028] In any embodiment, the coating layer includes one or more of carbon, silica, alumina, and titania.
[0029] As a result, the present application can obtain a coating layer with high integrity and density, thereby reducing the dissolution of free lithium in the lithium-rich core, reducing the side reactions of dissolving free lithium, increasing the charging capacity of the battery, reducing the resistance of the material, and increasing the migration rate of lithium ions.
[0030] In any embodiment, the mass content of the coating layer in the coated lithium-rich metal oxide material is 1.3% to 10%, and optionally 3% to 7%.
[0031] This is conducive to forming a uniform, complete and dense coating layer, reducing the dissolution of free lithium in the lithium-rich core, increasing battery capacity, reducing material resistance, and having a higher lithium ion migration rate.
[0032] In any embodiment, the particle size D of the coated lithium-rich metal oxide material v 50 is 2 to 10 μm, optionally 4 to 10 μm, and more optionally 4 to 8 μm.
[0033] In this way, the coated lithium-rich metal oxide material is ensured to have a suitable specific surface area, which ensures the stability, integrity and density of the coating layer, while being beneficial to the migration of lithium ions and improving the charging capacity of the battery.
[0034] In any embodiment, the mass content of water in the coated lithium-rich metal oxide material is ≤1000 ppm, optionally ≤500 ppm, more optionally ≤300 ppm, and further optionally ≤200 ppm.
[0035] As a result, the dissolution of free lithium in the lithium-rich core is further reduced, the side reactions of the dissolved lithium are further reduced, thereby further improving the migration of lithium ions, further improving the charging capacity of the battery, and further reducing the resistance of the material.
[0036] In any embodiment, the powder resistivity of the coated lithium-rich metal oxide material measured at a pressure of 20 MPa is less than 4 Ω·cm, and may be ≤3.3 Ω·cm. The reduction in resistivity is beneficial for increasing the migration rate of lithium ions and improving the charging capacity and rate of the battery.
[0037] The third aspect of the present application further provides a method for preparing a coated lithium-rich metal oxide material, comprising the following steps:
[0038] Provide compound Li z MO y’ , where 0.98≤z≤1.02, 2≤y'≤3;
[0039] Lithium ions were deposited by plasma enhanced chemical vapor deposition z MO y’ Carry out coating treatment;
[0040] The coated product is mixed with a lithium source and sintered to obtain a coated lithium-rich metal oxide material.
[0041] Plasma-enhanced chemical vapor deposition (PECVD) utilizes low-temperature plasma as an energy source. The substrate to be coated is placed on a cathode in a low-pressure glow discharge. The substrate is heated to a preset temperature using glow discharge or a heating element. An appropriate amount of reactive gas is then introduced, and a series of chemical and plasma reactions form a coating layer on the substrate. PECVD differs from conventional CVD methods in that low-temperature plasma contains a large number of high-energy electrons, which provide the activation energy required for the process. The collision of electrons with reactive gas molecules promotes molecular decomposition, combination, excitation, and ionization, generating a variety of highly active chemical groups and significantly reducing the temperature required for the coating process.
[0042] Therefore, the present invention adopts plasma enhanced chemical vapor deposition to deposit compound Li z MOy’ Coating treatment is performed, because the compound Li z MO y’ The lithium content is low, and the reaction gas in the coating process is not easy to react with the compound Li z MO y’ The lithium in the coating process produces no side reactions, ensuring the stability and effectiveness of the coating process. The coating product is mixed with lithium and then sintered to obtain a lithium-rich metal oxide material with high integrity and density of the coating layer. Furthermore, the method of the present application is simple to operate and easy to promote industrially.
[0043] In any embodiment, the coated lithium-rich metal oxide material includes a core and a coating layer covering the core, wherein the core includes Li a MO y , the coating layer includes one or more of carbon, silicon oxide and metal oxide;
[0044] Wherein, a, M and y are as in the first aspect or the second aspect of the present application.
[0045] In any embodiment, the coated lithium-rich metal oxide material is the coated lithium-rich metal oxide material of the first aspect or the second aspect of the present application.
[0046] In any embodiment, the operating parameters of the plasma enhanced chemical vapor deposition include:
[0047] The microwave power is 200-1000W, optionally 200-800W or 500-1000W; and / or,
[0048] The gas pressure in the chemical vapor deposition furnace is -10 to 1000 Pa, which can be 10 to 1000 Pa or -10 to 100 Pa; and / or,
[0049] The temperature inside the chemical vapor deposition furnace is 400° C. to 600° C., optionally 450° C. to 550° C.; and / or,
[0050] The deposition time is 2 to 10 hours, optionally 4 to 8 hours, more optionally 5 to 8 hours; and / or,
[0051] The gas flow rate at the gas inlet of the chemical vapor deposition furnace is 10 to 1000 sccm, optionally 100 to 700 sccm, and more optionally 200 to 500 sccm.
[0052] The microwave power within the above range is conducive to ensuring the ionization deposition rate of the reaction gas, forming a uniform, complete and dense coating layer on the surface of the coated object, and reducing the side reactions between the coated object and the reaction gas.
[0053] The furnace pressure within the above range can ensure the reaction rate of vapor deposition and ensure that the coating layer effectively covers the inner core, thereby forming a uniform, complete and dense coating layer and reducing the generation of defects.
[0054] The furnace temperature within the above range can increase the rate of ionized deposition of the reaction gas, forming a uniform, complete and dense coating layer on the surface of the coated object, while reducing the mass loss of the coated object caused by side reactions between the coated object and the reaction gas.
[0055] The deposition time within the above range is conducive to ensuring the appropriate content of the coating layer material and forming a uniform, complete and dense coating layer, which is conducive to the performance of the battery capacity.
[0056] The gas flow rate at the air inlet within the above range can ensure the appropriate content of the coating layer material, obtain a uniform, complete and dense coating layer, and reduce the waste of reaction gas.
[0057] In any embodiment, the raw materials used for the coating treatment are selected from one or more of a carbon source, a silicon oxide source, and a metal oxide source;
[0058] Optionally, the raw materials used for the coating treatment are selected from one or more of an organic carbon source, an organic silicon source, an inorganic silicon source, an organic aluminum source, an inorganic aluminum source, an organic titanium source and an inorganic titanium source, and more optionally selected from one or more of an organic gas, an organic silicon source, an organic aluminum source and an organic titanium source;
[0059] Optionally, the raw materials used for the coating treatment are selected from one or more of ethylene, acetylene, methane, acetone, ethanol, benzene, tetraethyl orthosilicate, silicon tetrachloride, aluminum isopropoxide, tetrabutyl titanate and titanium tetrachloride, and more optionally selected from one or more of ethylene, acetylene, methane, tetraethyl orthosilicate, aluminum isopropoxide and tetrabutyl titanate.
[0060] The raw materials used in the above coating treatment are conducive to forming a uniform, complete and dense coating layer on the surface of the coated object. At the same time, the above raw materials are not prone to side reactions in the coated object, thereby ensuring the effectiveness and stability of the coating treatment and reducing the waste of raw materials.
[0061] In any embodiment, the sintering temperature is 500° C. to 700° C., optionally 550° C. to 650° C., more optionally 600° C. to 650° C.; and / or,
[0062] The sintering time is 4 hours to 10 hours, optionally 6 hours to 8 hours, more optionally 6 hours to 7 hours; and / or,
[0063] The heating rate of sintering is 2°C / min to 8°C / min, optionally 4°C / min to 6°C / min; and / or,
[0064] Sintering is carried out in an inert atmosphere.
[0065] The sintering temperature, sintering time and sintering heating rate within the above ranges are conducive to obtaining a coated lithium-rich metal oxide with high crystallinity, reducing the generation of by-products and saving energy consumption.
[0066] In any embodiment, the lithium element in the lithium source and Li z MO y’ The molar ratio of (az): 1 is conducive to the formation of a lithium-rich metal oxide core, thereby obtaining a lithium-rich metal oxide material coated with a complete and dense coating layer.
[0067] In any embodiment, before the coating process, Li z MO y’ Crushing is beneficial to the uniformity of coating treatment and can ensure that the coated lithium-rich metal oxide material has a suitable specific surface area, thereby facilitating the migration of lithium ions and the utilization of battery capacity.
[0068] Prior to the coating process, the raw materials used in the coating process are gasified, optionally at 300° C. to 500° C. Non-gaseous raw materials need to be gasified to obtain the reaction gas required for the coating process to ensure the plasma-enhanced chemical vapor deposition process.
[0069] The prepared coated lithium-rich metal oxide material is crushed and sieved, optionally in a dry environment, to ensure that the coated lithium-rich metal oxide material has a suitable water content and particle size.
[0070] In any embodiment, Li z MO y’ Prepared by the following steps:
[0071] A lithium source and a source of element M are mixed and sintered; wherein the molar ratio of the lithium element in the lithium source to the element M in the source of element M is 0.98:1 to 1.09:1, optionally 0.98:1 to 1.02:1 or 1:1 to 1.09:1, and more optionally 1:1 to 1.05:1.
[0072] Since the compound Li z MO y’ The lithium content is low, so the compound Li z MO y’ The coating process has better stability and can achieve effective coating.
[0073] In any embodiment, the preparation of Li z MO y’ In the steps:
[0074] The sintering temperature is 400°C to 600°C, and can be optionally 450°C to 550°C; and / or,
[0075] The sintering time is 2 hours to 8 hours, and can be 4 hours to 6 hours; and / or,
[0076] The heating rate of sintering is 4°C / min to 10°C / min, and can be 6°C / min to 8°C / min; and / or,
[0077] Sintering is carried out in an inert atmosphere.
[0078] In any embodiment, the lithium source comprises one or more of lithium oxide, lithium carbonate, lithium oxalate, lithium acetate and lithium hydroxide; and / or,
[0079] The source of element M is selected from one or more of element M's oxides, hydroxides, halides, sulfates, carbonates, nitrates, oxalates, acetates, sulfides and nitrides, and may be element M's oxides.
[0080] A fourth aspect of the present application provides a method for measuring a coating layer in a coated lithium-rich metal oxide material, comprising the following steps:
[0081] Provide a coated lithium-rich metal oxide material, the coated lithium-rich metal oxide material includes a core and a coating layer covering the core, the core contains Li a MO y ; Wherein, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb and Cr, 2≤a≤6, 2≤y≤4; the coating layer comprises one or more selected from carbon, silicon oxide and metal oxide;
[0082] The coated lithium-rich metal oxide material and the solvent are mixed in a mass ratio of 1:50 to 1:1, and optionally in a mass ratio of 1:50 to 1:10, wherein the solvent consists of water and ethanol, the mass content of water in the solvent is b, and b satisfies: when 2≤a<3, b=100%-a×10%; when 3≤a<4, b=100%-a×20%; when 4≤a≤6, b=0;
[0083] The liquid phase in the obtained mixture is separated and titrated to calculate the free lithium content d dissolved in the coated lithium-rich metal oxide material to confirm whether the d value satisfies:
[0084] When 2≤a<3, d≤500ppm; when 3≤a<4, d≤1000ppm; when 4≤a≤6, d≤1500ppm.
[0085] According to the different lithium contents of the lithium-rich metal oxide core, this application uses solvents with different water contents (deionized water, anhydrous ethanol or a mixed solution of the two) to dissolve the free lithium in the material and react with the dissolved free lithium. The density and integrity of the coating layer are determined by measuring the free lithium content dissolved in the material. The measurement results are highly accurate, reliable and have a fast detection speed. At the same time, the coating layer can be prevented from being damaged during the measurement process.
[0086] In any embodiment, the mixing time is 1 min to 4 min, optionally 1 min to 3 min; and / or,
[0087] The mixing is carried out under stirring conditions of 200 rpm to 800 rpm, and optionally under stirring conditions of 400 rpm to 800 rpm; and / or,
[0088] The assay is performed at 25°C; and / or,
[0089] The titration is potentiometric.
[0090] The mixing time and stirring speed within the above range can ensure that the dissolved lithium of the coated lithium-rich metal oxide material reacts fully and effectively with the solvent, thereby ensuring the accuracy and reliability of the measurement results and avoiding damage to the coating layer.
[0091] In any embodiment, the free lithium content dissolved in the coated lithium-rich metal oxide material is determined by the following steps:
[0092] The coated lithium-rich metal oxide material and the solvent are mixed in a mass ratio of 1:50 to 1:1, and optionally in a mass ratio of 1:50 to 1:10, wherein the solvent consists of water and ethanol, the mass content of water in the solvent is b, and b satisfies: when 2≤a<3, b=100%-a×10%; when 3≤a<4, b=100%-a×20%; when 4≤a≤6, b=0;
[0093] Separate the liquid phase from the resulting mixture, take the liquid phase, and perform potentiometric titration using an ethanol solution of hydrochloric acid as the titrant. The titrant consumption volumes corresponding to the two potential jump points during the titration are V1 mL and V2 mL, respectively, and V2>V1.
[0094] The free lithium content d value dissolved in the coated lithium-rich metal oxide material is calculated according to the following formula:
[0095] d=C×V a ×(69.4684V2-0.0424V1) / (m×V b )
[0096] in,
[0097] m represents the mass of the coated lithium-rich metal oxide material, in g;
[0098] V a Indicates the volume of the solvent in mL;
[0099] V b Indicates the volume of the liquid phase taken, in mL;
[0100] C represents the concentration of hydrochloric acid in the titrant, in mol / L.
[0101] The fifth aspect of the present application provides a positive electrode plate, comprising the coated lithium-rich metal oxide material of the first aspect or the second aspect of the present application or the coated lithium-rich metal oxide material prepared according to the method of the third aspect of the present application.
[0102] The sixth aspect of the present application provides a battery, comprising the coated lithium-rich metal oxide material of the first aspect or the second aspect of the present application, the coated lithium-rich metal oxide material prepared according to the method of the third aspect of the present application, or the positive electrode sheet of the fifth aspect of the present application.
[0103] The seventh aspect of the present application provides an electrical device comprising the battery of the sixth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0104] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application.
[0105] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 1 .
[0106] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0107] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.
[0108] FIG. 5 is an exploded view of the battery pack shown in FIG. 4 according to an embodiment of the present application.
[0109] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0110] FIG7 is a TEM image of the lithium-rich metal oxide material prepared in Comparative Example 1.
[0111] FIG8 is a TEM image of the coated lithium-rich metal oxide material prepared in Example 1.
[0112] FIG9 is a TEM image of the coated lithium-rich metal oxide material prepared in Comparative Example 2.
[0113] Description of reference numerals:
[0114] 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0115] Hereinafter, the coated lithium-rich metal oxide material and its preparation method, the method for measuring the coating layer in the coated lithium-rich metal oxide material, the positive electrode plate, the battery and the implementation method of the electric device of the present application will be described in detail with appropriate reference to the accompanying drawings. However, there will be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0116] The "ranges" disclosed herein are defined in terms of lower and upper limits, where a given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive of the end values and can be combined arbitrarily, i.e., any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 to 120 and 80 to 110 are listed for a particular parameter, it is understood that ranges of 60 to 110 and 80 to 120 are also contemplated. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, the following ranges are all contemplated: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5. In this application, unless otherwise indicated, the numerical range "a to b" is a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0117] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0118] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0119] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0120] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.
[0121] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0122] [Secondary battery]
[0123] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged to activate the active materials after discharge and continue to be used.
[0124] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the battery's charge and discharge process, active ions (such as lithium ions) are embedded and released back and forth between the positive and negative electrode sheets. The separator is set between the positive and negative electrode sheets, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte between the positive and negative electrode sheets mainly plays the role of conducting active ions.
[0125] [Coated lithium-rich metal oxide materials]
[0126] One embodiment of the present application provides a coated lithium-rich metal oxide material, comprising a core and a coating layer coating the core;
[0127] The core contains Li a MO y ; Wherein, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb and Cr, 2≤a≤6, 2≤y≤4;
[0128] The coating layer comprises one or more of carbon, silicon oxide, and metal oxide;
[0129] The weight growth rate of the coated lithium-rich metal oxide material after standing in an environment of 25° C. and 40% relative humidity for 144 to 192 hours (e.g., 168 hours) is w, w<0.8%;
[0130] Optionally, w≤0.5%.
[0131] Although the mechanism is still unclear, the inventors have found that the coated lithium-rich metal oxide material of the present application has a coating layer with high integrity and density, which blocks and reduces the dissolution of free lithium in the lithium-rich metal oxide core, reduces the loss of active lithium, and improves the battery's charging capacity. Since the dissolved free lithium easily reacts with external substances to generate highly alkaline byproducts, the byproducts easily cause slurry gel, hindering the migration of lithium ions and battery processing, and increasing the material resistance. Therefore, the coating layer of the coated lithium-rich metal oxide material of the present application reduces the dissolution of free lithium, thereby improving the mobility of lithium ions, reducing the material resistance, and being more conducive to the processing of battery products.
[0132] Another embodiment of the present application provides a coated lithium-rich metal oxide material, comprising a core and a coating layer coating the core;
[0133] The core contains Li a MO y ; Wherein, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb and Cr, 2≤a≤6, such as 2, 3, 4, 5, 6 and the range formed by any two of the above values, 2≤y≤4, such as 2, 3, 4 and the range formed by any two of the above values;
[0134] The coating layer comprises one or more of carbon, silicon oxide, and metal oxide;
[0135] Moreover, the d value of the coated lithium-rich metal oxide material satisfies:
[0136] When 2≤a<3, d≤500ppm;
[0137] When 3≤a<4, d≤1000ppm;
[0138] When 4≤a≤6, d≤1500ppm;
[0139] The d value of the coated lithium-rich metal oxide material is determined by the following steps:
[0140] The coated lithium-rich metal oxide material and the solvent are mixed at a mass ratio of 1:50 to 1:1 (e.g., 1:1, 1:10, 1:20, 1:40, and a range formed by any two of the above values), wherein the solvent is composed of water and ethanol, the mass content of water in the solvent is b, and b satisfies:
[0141] When 2≤a<3, b=100%-a×10%;
[0142] When 3≤a<4, b=100%-a×20%;
[0143] When 4≤a≤6, b=0;
[0144] The liquid phase in the obtained mixture is separated and subjected to potentiometric titration to calculate the free lithium content dissolved in the coated lithium-rich metal oxide material, which is the d value of the coated lithium-rich metal oxide material.
[0145] Therefore, on the basis of the first embodiment, the integrity and density of the coating layer in the coated lithium-rich metal oxide material of the present application are further improved, the dissolution of free lithium in the lithium-rich metal oxide core is further reduced, and the side reactions of the dissolved free lithium with external substances are further reduced, thereby further improving the capacity of the battery, further improving the migration rate of lithium ions, and further reducing the resistance of the material.
[0146] In some embodiments, M includes one or more elements of Ni, Co, Fe, Mn, Cu, V, and Nb, and optionally includes one or more elements of Ni, Co, Fe, Cu, and Nb.
[0147] In some embodiments, the inner core includes one or more of Li2NiO2, Li2CuO2, Li2MnO3, Li3VO4, Li3NbO4, Li5FeO4 and Li6CoO4, and optionally includes one or more of Li2NiO2, Li2CuO2, Li3NbO4, Li5FeO4 and Li6CoO4.
[0148] In some embodiments, the coating layer includes one or more of carbon, silica, alumina, and titania.
[0149] As a result, the present application can obtain a coating layer with high integrity and density, thereby reducing the dissolution of free lithium in the lithium-rich core, reducing the side reactions of dissolving free lithium, increasing the charging capacity of the battery, reducing the resistance of the coated lithium-rich metal oxide material, and increasing the migration rate of lithium ions.
[0150] In some embodiments, the mass content of the coating layer in the coated lithium-rich metal oxide material is 1.3% to 10%, optionally 3% to 7%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and the range formed by any two of the above values.
[0151] This is conducive to forming a uniform, complete and dense coating layer, reducing the dissolution of free lithium in the lithium-rich core, increasing battery capacity, reducing material resistance, and having a higher lithium ion migration rate.
[0152] In some embodiments, the particle size D of the coated lithium-rich metal oxide material is v 50 is 2 to 10 μm, and can be optionally 4 to 10 μm, and more optionally 4 to 8 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, and the range formed by any two of the above values.
[0153] In this way, the coated lithium-rich metal oxide material is ensured to have a suitable specific surface area, which ensures the stability, integrity and density of the coating layer, while being beneficial to the migration of lithium ions and improving the charging capacity of the battery.
[0154] In some embodiments, the mass content of water in the coated lithium-rich metal oxide material is ≤1000 ppm, optionally ≤500 ppm, more optionally ≤400 ppm or ≤300 ppm, further optionally ≤200 ppm, and further optionally ≤100 ppm.
[0155] As a result, the dissolution of free lithium in the lithium-rich core is further reduced, the side reactions of the dissolved lithium are further reduced, thereby further improving the migration of lithium ions, further improving the charging capacity of the battery, and further reducing the resistance of the material.
[0156] In some embodiments, the powder resistivity of the coated lithium-rich metal oxide material measured at a pressure of 20 MPa is less than 4 Ω·cm, and may be ≤3.3 Ω·cm, more preferably ≤3 Ω·cm, ≤2 Ω·cm, or ≤1 Ω·cm. This reduction in resistivity helps increase the migration rate of lithium ions, thereby improving the battery's charge capacity and charge rate.
[0157] [Preparation method of coated lithium-rich metal oxide material]
[0158] One embodiment of the present application provides a method for preparing a coated lithium-rich metal oxide material, comprising the following steps:
[0159] Provide compound Li z MO y’ , where 0.98≤z≤1.02, 2≤y'≤3;
[0160] Lithium ions were deposited by plasma enhanced chemical vapor deposition z MO y’ Carry out coating treatment;
[0161] The coated product is mixed with a lithium source and sintered to obtain a coated lithium-rich metal oxide material.
[0162] Plasma-enhanced chemical vapor deposition (PECVD) utilizes low-temperature plasma as an energy source. The substrate to be coated is placed on a cathode in a low-pressure glow discharge. The substrate is heated to a preset temperature using glow discharge or a heating element. An appropriate amount of reactive gas is then introduced, and a series of chemical and plasma reactions form a coating layer on the substrate. PECVD differs from conventional CVD methods in that low-temperature plasma contains a large number of high-energy electrons, which provide the activation energy required for the process. The collision of electrons with reactive gas molecules promotes molecular decomposition, combination, excitation, and ionization, generating a variety of highly active chemical groups and significantly reducing the temperature required for the coating process.
[0163] Therefore, the present invention adopts plasma enhanced chemical vapor deposition to deposit compound Li z MO y’ Coating treatment is performed, because the compound Li z MO y’ The lithium content is low, the stability is high, and the temperature required for plasma enhanced chemical vapor deposition is low. The reaction gas in the coating process is not easy to react with the compound Li z MO y’ The lithium in the coating is reacted with the lithium to produce a side reaction, ensuring the stability and effectiveness of the coating process. The coated product is mixed with lithium and then sintered to obtain a lithium-rich metal oxide material with high integrity and density of the coating layer. In addition, the method of the application is simple to operate and easy to promote industrialization.
[0164] In some embodiments, the coated lithium-rich metal oxide material includes a core and a coating layer coating the core, wherein the core includes Li a MO y , the coating layer includes one or more of carbon, silicon oxide and metal oxide;
[0165] Wherein, a, M and y are as in the [coated lithium-rich metal oxide material] of this application;
[0166] In some embodiments, the coated lithium-rich metal oxide material is as described in [Coated lithium-rich metal oxide material] of the present application.
[0167] In some embodiments, operating parameters for plasma enhanced chemical vapor deposition include:
[0168] The microwave power is 200-1000 W, optionally 200-800 W or 500-1000 W, for example, 200 W, 300 W, 400 W, 500 W, 600 W, 700 W, 800 W, 900 W, 1000 W or a range formed by any two of the above values; and / or,
[0169] The gas pressure in the chemical vapor deposition furnace is -10 to 1000 Pa, which can be selected from 10 to 1000 Pa or -10 to 100 Pa, for example, -10 Pa, 0 Pa, 10 Pa, 20 Pa, 50 Pa, 100 Pa, 150 Pa, 200 Pa, 300 Pa, 400 Pa, 500 Pa, 600 Pa, 700 Pa, 800 Pa, 900 Pa, 1000 Pa or a range formed by any two of the above values; and / or,
[0170] The temperature in the chemical vapor deposition furnace is 400° C. to 600° C., optionally 450° C. to 550° C., for example, 400° C., 450° C., 500° C., 550° C., 600° C., or a range formed by any two of the above values; and / or,
[0171] The deposition time is 2 to 10 hours, optionally 4 to 8 hours, more optionally 5 to 8 hours, for example 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours or a range formed by any two of the above values; and / or,
[0172] The gas flow rate at the inlet of the chemical vapor deposition furnace is 10 to 1000 sccm, optionally 100 to 700 sccm, and more optionally 200 to 500 sccm, for example, 20 sccm, 50 sccm, 100 sccm, 200 sccm, 300 sccm, 400 sccm, 500 sccm, 600 sccm, 700 sccm, 800 sccm, 900 sccm, 1000 sccm or a range formed by any two of the above values.
[0173] The above “sccm” represents the flow rate unit under standard atmospheric pressure—ml / minute.
[0174] The microwave power within the above range is conducive to ensuring the ionization deposition rate of the reaction gas, forming a uniform, complete and dense coating layer on the surface of the coated object, and reducing the side reactions between the coated object and the reaction gas.
[0175] The furnace pressure within the above range can ensure the reaction rate of vapor deposition and ensure that the coating layer effectively covers the core, thereby forming a uniform, complete and dense coating layer and reducing the occurrence of defects.
[0176] The furnace temperature within the above range can increase the rate of ionized deposition of the reaction gas, forming a uniform, complete and dense coating layer on the surface of the coated object, while reducing the mass loss of the coated object caused by side reactions between the coated object and the reaction gas.
[0177] The deposition time within the above range is conducive to ensuring the appropriate content of the coating layer material and forming a uniform, complete and dense coating layer, which is conducive to the performance of the battery capacity.
[0178] The gas flow rate at the air inlet within the above range can ensure the appropriate content of the coating layer material, obtain a uniform, complete and dense coating layer, and reduce the waste of reaction gas.
[0179] In some embodiments, the raw materials used in the coating process are selected from one or more of a carbon source, a silicon oxide source, and a metal oxide source;
[0180] Optionally, the raw materials used for the coating treatment are selected from one or more of an organic carbon source, an organic silicon source, an inorganic silicon source, an organic aluminum source, an inorganic aluminum source, an organic titanium source and an inorganic titanium source, and more preferably selected from one or more of an organic gas, an organic silicon source, an organic aluminum source and an organic titanium source;
[0181] Optionally, the raw materials used for the coating treatment are selected from one or more of ethylene, acetylene, methane, acetone, ethanol, benzene, tetraethyl orthosilicate, silicon tetrachloride, aluminum isopropoxide, tetrabutyl titanate and titanium tetrachloride, and more optionally selected from one or more of ethylene, acetylene, methane, tetraethyl orthosilicate, aluminum isopropoxide and tetrabutyl titanate.
[0182] The raw materials used in the above coating treatment are conducive to forming a uniform, complete and dense coating layer on the surface of the coated object. At the same time, the above raw materials are not prone to side reactions in the coated object, thereby ensuring the effectiveness and stability of the coating treatment and reducing the waste of raw materials.
[0183] In some embodiments, the sintering temperature is 500°C to 700°C, optionally 550°C to 650°C, more optionally 600°C to 650°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, or a range formed by any two of the above values; and / or,
[0184] The sintering time is 4 hours to 10 hours, optionally 6 hours to 8 hours, more optionally 6 hours to 7 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours or a range formed by any two of the above values; and / or,
[0185] The sintering heating rate is 2°C / min to 8°C / min, and can be 4°C / min to 6°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, or a range formed by any two of the above values; and / or,
[0186] Sintering is carried out in an inert atmosphere.
[0187] The sintering temperature, sintering time and sintering heating rate within the above ranges are conducive to obtaining a coated lithium-rich metal oxide with high crystallinity, reducing the generation of by-products and saving energy consumption.
[0188] In some embodiments, the lithium element in the lithium source and Li z MO y’ The molar ratio of (az): 1 is conducive to the formation of a lithium-rich metal oxide core, thereby obtaining a lithium-rich metal oxide material coated with a complete and dense coating layer.
[0189] In some embodiments, prior to the coating process, Li z MO y’ Crushing is beneficial to the uniformity of coating treatment and can ensure that the coated lithium-rich metal oxide material has a suitable specific surface area, thereby facilitating the migration of lithium ions and the utilization of battery capacity.
[0190] Prior to the coating process, the raw materials used in the coating process are gasified, optionally at 300° C. to 500° C. Non-gaseous raw materials need to be gasified to obtain the reaction gas required for the coating process to ensure the plasma-enhanced chemical vapor deposition process.
[0191] The prepared coated lithium-rich metal oxide material is crushed and sieved, optionally in a dry environment, to ensure that the coated lithium-rich metal oxide material has a suitable water content and particle size.
[0192] In some embodiments, Li z MO y’ Prepared by the following steps:
[0193] A lithium source and a source of element M are mixed and sintered; wherein the molar ratio of the lithium element in the lithium source to the element M in the source of element M is 0.98:1 to 1.09:1, optionally 0.98:1 to 1.02:1 or 1:1 to 1.09:1, more optionally 1:1 to 1.05:1, and further optionally 1:1 to 1.02:1.
[0194] Since the compound Li z MO y’ The lithium content is low, so the compound Liz MO y’ The coating process has better stability and can achieve effective coating.
[0195] In some embodiments, the preparation of Li z MO y’ In the steps:
[0196] The sintering temperature is 400° C. to 600° C., and may be 450° C. to 550° C., for example, 400° C., 450° C., 500° C., 550° C., 600° C., or a range formed by any two of the above values; and / or,
[0197] The sintering time is 2 hours to 8 hours, and can be 4 hours to 6 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, or a range formed by any two of the above values; and / or,
[0198] The sintering heating rate is 4°C / min to 10°C / min, and can be 6°C / min to 8°C / min, for example, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or a range formed by any two of the above values; and / or,
[0199] Sintering is carried out in an inert atmosphere.
[0200] In some embodiments, the lithium source comprises one or more of lithium oxide, lithium carbonate, lithium oxalate, lithium acetate, and lithium hydroxide; and / or,
[0201] The source of element M is selected from one or more of element M's oxides, hydroxides, halides, sulfates, carbonates, nitrates, oxalates, acetates, sulfides and nitrides, and may be element M's oxides.
[0202] [Method for Determining the Coating Layer in Coated Lithium-Rich Metal Oxide Materials]
[0203] One embodiment of the present application provides a method for measuring a coating layer in a coated lithium-rich metal oxide material, comprising the following steps:
[0204] Provided is a coated lithium-rich metal oxide material, comprising a core and a coating layer covering the core, wherein the core comprises Li a MO y ; Wherein, M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb and Cr, 2≤a≤6, 2≤y≤4; the coating layer comprises one or more selected from carbon, silicon oxide and metal oxide;
[0205] The coated lithium-rich metal oxide material is mixed with a solvent in a mass ratio of 1:50 to 1:1 (a mass ratio of 1:50 to 1:10 can be selected, for example, 1:1, 1:10, 1:20, 1:40, and a range formed by any two of the above values), wherein the solvent is composed of water and ethanol, the mass content of water in the solvent is b, and b satisfies: when 2≤a<3, b=100%-a×10%; when 3≤a<4, b=100%-a×20%; when 4≤a≤6, b=0;
[0206] The liquid phase in the obtained mixture is separated and titrated to calculate the free lithium content d dissolved in the coated lithium-rich metal oxide material to confirm whether the d value satisfies:
[0207] When 2≤a<3, d≤500ppm; when 3≤a<4, d≤1000ppm; when 4≤a≤6, d≤1500ppm.
[0208] Optionally, if the d value satisfies the above conditions, the integrity and density of the coating layer of the coated lithium-rich metal oxide material are good; otherwise, the integrity and density of the coating layer of the coated lithium-rich metal oxide material are poor.
[0209] The present application adopts solvents with different water contents (deionized water, anhydrous ethanol or a solution of the two mixed in a specific ratio) to dissolve the free lithium in the coated lithium-rich metal oxide material according to the different lithium contents of the lithium-rich metal oxide core and react with the dissolved free lithium. The density and integrity of the coating layer are determined by measuring the free lithium content dissolved from the coated lithium-rich metal oxide material. The measurement results are highly accurate, reliable and have a fast detection speed. At the same time, the coating layer can be prevented from being damaged during the measurement process.
[0210] In some embodiments, the titration can be performed by any common titration method in the art, and can be potentiometric titration.
[0211] In some embodiments, the mixing time is 1 min to 4 min, optionally 1 min to 3 min, for example, 1 min, 2 min, 3 min, 4 min, or a range formed by any two of the above values; and / or,
[0212] The mixing is carried out under stirring conditions of 200 rpm to 800 rpm, optionally 400 rpm to 800 rpm, for example 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm or a range formed by any two of the above values; and / or,
[0213] The assay was performed at 25°C.
[0214] The mixing time and stirring speed within the above range can ensure that the dissolved lithium of the coated lithium-rich metal oxide material reacts fully and effectively with the solvent, thereby ensuring the accuracy and reliability of the measurement results and avoiding damage to the coating layer.
[0215] In some embodiments, the free lithium content dissolved in the coated lithium-rich metal oxide material is determined by the following steps:
[0216] The coated lithium-rich metal oxide material is mixed with a solvent in a mass ratio of 1:50 to 1:1 (optionally a mass ratio of 1:50 to 1:10), wherein the solvent consists of water and ethanol, the mass content of water in the solvent is b, and b satisfies: when 2≤a<3, b=100%-a×10%; when 3≤a<4, b=100%-a×20%; when 4≤a≤6, b=0;
[0217] Separate the liquid phase from the resulting mixture, take the liquid phase, and perform potentiometric titration using an ethanol solution of hydrochloric acid as the titrant. The titrant consumption volumes corresponding to the two potential jump points during the titration are V1 mL and V2 mL, respectively, and V2>V1.
[0218] The free lithium content d value dissolved in the coated lithium-rich metal oxide material is calculated according to the following formula:
[0219] d=C×V a ×(69.4684V2-0.0424V1) / (m×V b )
[0220] in,
[0221] m represents the mass of the coated lithium-rich metal oxide material, in g;
[0222] V a Indicates the volume of the solvent in mL;
[0223] V b Indicates the volume of the liquid phase taken, in mL;
[0224] C represents the concentration of hydrochloric acid in the titrant, in mol / L.
[0225] In some embodiments, during the potentiometric titration process, a graph is drawn with the pH value during the titration process as the ordinate and the volume of titrant consumed as the abscissa. V1 and V2 refer to the titrant consumption volumes corresponding to the two potential jump points in the graph, and V2>V1.
[0226] [Positive electrode]
[0227] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector. The positive electrode film layer includes the aforementioned coated lithium-rich metal oxide material or the coated lithium-rich metal oxide material prepared by the aforementioned method.
[0228] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0229] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0230] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0231] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0232] In some embodiments, the positive electrode sheet can be prepared by the following method: dispersing the above components for preparing the positive electrode sheet in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0233] [Negative electrode]
[0234] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0235] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0236] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0237] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0238] In some embodiments, the negative electrode film layer may further include a binder. For example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0239] In some embodiments, the negative electrode film layer may further include a conductive agent. For example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0240] In some embodiments, the negative electrode film layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0241] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0242] [Electrolytes]
[0243] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0244] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.
[0245] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0246] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0247] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0248] [Isolation film]
[0249] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0250] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0251] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0252] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0253] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0254] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 5 with a square structure as an example.
[0255] In some embodiments, referring to FIG2 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0256] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0257] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0258] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of secondary batteries 5 are accommodated in the accommodation space.
[0259] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0260] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0261] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0262] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0263] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0264] [Example]
[0265] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0266] Example 1
[0267] 1. Preparation of coated lithium-rich metal oxide materials:
[0268] Mixing lithium hydroxide and ferric oxide, wherein the molar ratio of lithium in the lithium hydroxide to iron in the ferric oxide is 1.05:1, heating to 500°C in nitrogen for a single sintering at a heating rate of 7°C / min and a sintering time of 5 hours, to obtain an intermediate product, LiFeO2;
[0269] The intermediate product LiFeO2 was airflow-broken and then placed in a plasma-enhanced chemical vapor deposition furnace for coating treatment. The raw material gas, ethylene, was introduced into the furnace at a gas flow rate of 400 sccm (standard milliliters per minute), the furnace temperature was 500°C, the furnace pressure was 10 Pa, the deposition time was 6 hours, and the microwave power was 500 W. The organic gas was decomposed in the furnace and then deposited on the surface of the intermediate product LiFeO2 to obtain carbon-coated LiFeO2;
[0270] The carbon-coated LiFeO2 was mixed with a lithium source (the lithium source was the same as mentioned above), the molar ratio of lithium element in the lithium source to LiFeO2 was 4:1, and the temperature was raised to 600°C for secondary sintering at a heating rate of 5°C / min and a sintering time of 7h. After sintering, the mixture was crushed and sieved in a dry environment to obtain carbon-coated Li5FeO4.
[0271] 2. Preparation of positive electrode sheets: The above-mentioned coated lithium-rich metal oxide material, binder polyvinylidene fluoride (PVDF), and conductive agent acetylene black are dissolved in solvent N-methylpyrrolidone (NMP) in a mass ratio of 97:2:1, and the mixture is thoroughly stirred and mixed to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then dried, cold pressed, and cut to obtain positive electrode sheets.
[0272] 3. Preparation of negative electrode sheets: Dissolve the negative electrode active material artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) in deionized water at a mass ratio of 96:1.5:1.5:1.0, stir and mix thoroughly to prepare a negative electrode slurry; coat the negative electrode slurry on the negative electrode current collector copper foil, and then dry, cold press, and cut to obtain a negative electrode sheet.
[0273] 4. Isolation film: polypropylene film.
[0274] 5. Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte. The concentration of LiPF6 in the electrolyte was 1 mol / L.
[0275] 6. Preparation of secondary batteries: stack and wind the above-mentioned positive electrode sheets, separators, and negative electrode sheets in order to obtain an electrode assembly; place the electrode assembly in an outer package, add the above-prepared electrolyte, and obtain a secondary battery after packaging, standing, formation, aging and other processes.
[0276] The secondary battery preparation methods of Examples 2 to 33 and Comparative Examples 1 to 19 are similar to those of Example 1, but the parameters and compositions are adjusted. The different parameters are detailed in Table 1.
[0277]
[0278]
[0279] Performance Testing
[0280] (1) Determination of coating content in coated lithium-rich metal oxide materials:
[0281] If the coating layer is carbon, a high-frequency infrared carbon and sulfur analyzer (C content analyzer, model HCS-140, Shanghai Dekai Instrument Co., Ltd.) is used to test the coating layer content in the coated lithium-rich metal oxide material in accordance with GBT20123-2006 "Determination of total carbon and sulfur content of steel using infrared absorption method after combustion in a high-frequency induction furnace (conventional method)".
[0282] If the coating is an oxide M x O y The coating content was determined by ICP (inductively coupled plasma) atomic emission spectrometry using an inductively coupled plasma atomic emission spectrometer (model ICAP7400, Thermo Fisher Scientific, USA), specifically:
[0283] The coated lithium-rich metal oxide material was added to aqua regia and digested under mechanical stirring for 30 minutes. The digested solution was added to an ICAP7400 spectrometer to quantitatively analyze the chemical composition elements in the coated lithium-rich metal oxide material. The mass fraction p of the M element was measured, and the content of the coating layer was calculated according to the following formula:
[0284] Coating content = 100% × (n × p) / m,
[0285] Where n represents M x O y The relative molecular mass of M, m represents the relative atomic mass of M.
[0286] (2) Determination of particle size Dv50 of coated lithium-rich metal oxide material:
[0287] The particle size distribution was determined by laser diffraction method according to GB / T 19077-2016 using a laser particle size analyzer (Malvern Panalytical Mastersizer 2000E).
[0288] Dv50 can be adjusted by controlling the degree of crushing and screening of the coated lithium-rich metal oxide material.
[0289] (3) Determination of water content in coated lithium-rich metal oxide materials:
[0290] Using a Karl Fischer moisture analyzer (Model 831, Metrohm, Switzerland), 10 g of the coated lithium-rich metal oxide material was heated at 170°C in the fully automatic Karl Fischer sample heater (Model 874, Metrohm, Switzerland) provided with the above-mentioned analyzer, and purged with dry nitrogen at a flow rate of 40 mL / min. The titration time was 400 s.
[0291] The water content can be adjusted by crushing and screening the coated lithium-rich metal oxide material under different humidity environments.
[0292] (4) TEM images of the lithium-rich metal oxide material of Comparative Example 1 and the coated lithium-rich metal oxide materials of Example 1 and Comparative Example 2 are shown in Figures 7 to 9, respectively.
[0293] (5) Determination of the first charge capacity of secondary batteries:
[0294] The assembled secondary battery was charged at a constant current of 0.1C to 4.25V, left to stand for 5 minutes, and the first-cycle charging capacity of the secondary battery was recorded. The first-cycle charging capacity of the secondary battery was obtained by dividing the first-cycle charging capacity of the battery by the mass of the coated lithium-rich metal oxide material used.
[0295] (6) Determination of powder resistivity of coated lithium-rich metal oxide materials:
[0296] The powder of the coated lithium-rich metal oxide material was dried, and an appropriate amount of powder was weighed. The powder resistivity of the sample was then measured using a powder resistivity tester (ST2722 digital four-probe tester, Suzhou Jingge Electronics Co., Ltd.) in accordance with GB / T 30835-2014 "Carbon-composite lithium iron phosphate cathode material for lithium-ion batteries" at a test pressure of 20 MPa.
[0297] (7) Stability test of coated lithium-rich metal oxide materials:
[0298] Take s(g) of the coated lithium-rich metal oxide material and place it in a constant temperature (25°C) and constant humidity (relative humidity of 40%) environment for 7 days. Then weigh the sample to obtain the mass t(g). Calculate the weight growth rate w according to the following formula:
[0299] Weight growth rate w = 100% × (ts) / t
[0300] w≤0.5%, indicating that the integrity and density of the coating layer are excellent; 0.5%<w<0.8%, indicating that the integrity and density of the coating layer are good; w≥0.8%, indicating that the integrity and density of the coating layer are poor.
[0301] (8) Test of coating integrity and density of coated lithium-rich metal oxide materials:
[0302] At 25°C, take m (g) of coated lithium-rich metal oxide material in a beaker and add V a (mL) mixed solvent of deionized water and anhydrous ethanol, wherein the mass proportion of deionized water in the mixed solvent is b, and b satisfies:
[0303] When 2≤a<3, b=100%-a×10%;
[0304] When 3≤a<4, b=100%-a×20%;
[0305] When 4≤a≤6, b=0;
[0306] After sealing with sealing film, the above mixed system was stirred at a speed of 600 rpm for 3 min, and then filtered using a vacuum filtration device after standing. b (mL) filtrate, titrate the filtrate with ethanol solution of hydrochloric acid (hydrochloric acid concentration is C mol / L), start the automatic potentiometric titrator, titrate with pH value as the vertical axis and titrant consumption volume as the horizontal axis, record the jump points EP1 and EP2 of the electrode potential, and the titrant consumption volumes corresponding to the two jump points are V1 (mL) and V2 (mL) respectively (V2>V1); wherein,
[0307] When the titration reaction reaches the electrode potential jump point EP1, the following chemical reaction occurs:
[0308] LiOH + HCl → LiCl + H2O
[0309] Li2CO3+HCl→LiCl+LiHCO3
[0310] When the titration reaction reaches the electrode potential jump point EP2, the following chemical reaction occurs:
[0311] LiHCO3+HCl→LiCl+H2O+CO2
[0312] The free lithium content d (ppm) dissolved in m (g) coated lithium-rich metal oxide material is calculated according to the following formula:
[0313] d=C×V a ×(69.4684V2-0.0424V1) / (m×V b )
[0314] If the d value satisfies the following conditions, the integrity and density of the coating are good, otherwise the integrity and density of the coating are poor:
[0315] When 2≤a<3, d≤500ppm;
[0316] When 3≤a<4, d≤1000ppm;
[0317] When 4≤a≤6, d≤1500ppm.
[0318] The above results are shown in Table 2.
[0319]
[0320]
[0321] From Table 1-2 we can see that:
[0322] Compared to Comparative Examples 1-8, the coating layer in the coated lithium-rich metal oxide materials of the present application exhibits improved integrity and density. Specifically, the coating layer integrity and density of the coated lithium-rich metal oxide materials of Examples 1-29 of the present application are further improved. Compared to Comparative Examples 6-8, the coating layer material content in the coated lithium-rich metal oxide materials of the present application is higher.
[0323] Compared with comparative examples 1-2, the powder resistivity of the coated lithium-rich metal oxide materials of Examples 1-5 and 13-15 of the present application is lower, and the first-cycle charging capacity of the secondary battery is higher.
[0324] Compared with comparative examples 3-5, the powder resistivity of the coated lithium-rich metal oxide materials in Examples 24-26 of the present application is lower, and the first-cycle charging capacity of the secondary battery is higher.
[0325] Compared with comparative examples 6-8, the powder resistivity of the coated lithium-rich metal oxide materials prepared in Examples 1-2, 5, 15, 30 and 33 of the present application using a microwave power of 200 to 1000 W and a furnace pressure of -10 to 1000 Pa is lower, and the first-cycle charging gram capacity of the secondary battery is higher.
[0326] The results of comparative examples 9-14 using deionized water as the solvent (b=100%) to measure the integrity and density of the coating layer deviate greatly from the results of the stability test. In comparison, the results of comparative examples 1-2 and Examples 1 and 37-39 of the present application using suitable solvents to measure the integrity and density of the coating layer are consistent with the results of the stability test.
[0327] The results of the coating integrity and density measured by comparative examples 15-19 using an excessively low ratio of coating-type lithium-rich metal oxide material and solvent deviate greatly from the stability test results. In comparison, the results of the coating integrity and density measured by embodiments 1 and 13-14 using an appropriate ratio of coating-type lithium-rich metal oxide material and solvent are consistent with the stability test results.
[0328] The above description shows that the coating layer in the coated lithium-rich metal oxide material of the present application has better integrity and density, lower powder resistivity, better conductivity, higher coating layer material content, and higher first-cycle charging capacity of the secondary battery.
[0329] Since the stability test is an existing method, the results of the method of the present application for determining the integrity and density of the coating layer in the coated lithium-rich metal oxide material are consistent with the stability test results, indicating that the determination method of the present application has high accuracy.
[0330] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A coated lithium-rich metal oxide material comprising a core and a coating layer coating the core; The core contains Li a MO y ;in, The M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb and Cr, 2≤a≤6, 2≤y≤4; The coating layer comprises one or more of carbon, silicon oxide and metal oxide; The weight growth rate of the coated lithium-rich metal oxide material after standing in an environment of 25° C. and 40% relative humidity for 144 to 192 hours is w, wherein w is less than 0.8%; Optionally, w≤0.5%.
2. A coated lithium-rich metal oxide material comprising a core and a coating layer coating the core; The core contains Li a MO y ;in, The M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb and Cr, 2≤a≤6, 2≤y≤4; The coating layer comprises one or more of carbon, silicon oxide and metal oxide; Furthermore, the d value of the coated lithium-rich metal oxide material satisfies: When 2≤a<3, d≤500ppm; When 3≤a<4, d≤1000ppm; When 4≤a≤6, d≤1500ppm; The d value of the coated lithium-rich metal oxide material is determined by the following steps: The coated lithium-rich metal oxide material is mixed with a solvent in a mass ratio of 1:50 to 1:1, wherein the solvent consists of water and ethanol, the mass content of the water in the solvent is b, and b satisfies: When 2≤a<3, b=100%-a×10%; When 3≤a<4, b=100%-a×20%; When 4≤a≤6, b=0; The liquid phase in the obtained mixture is separated and subjected to potentiometric titration to calculate the free lithium content dissolved in the coated lithium-rich metal oxide material, which is the d value of the coated lithium-rich metal oxide material.
3. The coated lithium-rich metal oxide material according to claim 1 or 2, wherein: The M includes one or more elements selected from the group consisting of Ni, Co, Fe, Mn, Cu, V, and Nb, and may optionally include one or more elements selected from the group consisting of Ni, Co, Fe, Cu, and Nb.
4. The coated lithium-rich metal oxide material according to any one of claims 1 to 3, wherein The core includes one or more of Li2NiO2, Li2CuO2, Li2MnO3, Li3VO4, Li3NbO4, Li5FeO4 and Li6CoO4, and optionally includes one or more of Li2NiO2, Li2CuO2, Li3NbO4, Li5FeO4 and Li6CoO4.
5. The coated lithium-rich metal oxide material according to any one of claims 1 to 4, wherein The coating layer includes one or more of carbon, silicon dioxide, aluminum oxide and titanium oxide.
6. The coated lithium-rich metal oxide material according to any one of claims 1 to 5, wherein The coating layer has a mass content of 1.3% to 10% in the coated lithium-rich metal oxide material, and can optionally be 3% to 7%.
7. The coated lithium-rich metal oxide material according to any one of claims 1 to 6, wherein The particle size D of the coated lithium-rich metal oxide material v 50 is 2 to 10 μm, optionally 4 to 10 μm, and more optionally 4 to 8 μm.
8. The coated lithium-rich metal oxide material according to any one of claims 1 to 7, wherein The mass content of water in the coated lithium-rich metal oxide material is ≤1000 ppm, can be optionally ≤500 ppm, more can be optionally ≤300 ppm, and further can be optionally ≤200 ppm.
9. The coated lithium-rich metal oxide material according to any one of claims 1 to 8, wherein The powder resistivity of the coated lithium-rich metal oxide material measured at a pressure of 20 MPa is less than 4 Ω·cm, and can be optionally ≤3.3 Ω·cm.
10. A method for preparing a coated lithium-rich metal oxide material, comprising the following steps: Provide compound Li z MO y’ ,in, 0.98≤z≤1.02, 2≤y'≤3; The Li z MO y’ Carry out coating treatment; The coated product is mixed with a lithium source and sintered to obtain a coated lithium-rich metal oxide material.
11. The method according to claim 10, wherein: The coated lithium-rich metal oxide material comprises a core and a coating layer covering the core, wherein the core comprises Li a MO y , the coating layer includes one or more of carbon, silicon oxide and metal oxide; Wherein, a, M and y are as described in any one of claims 1 to 9.
12. The method according to claim 10 or 11, wherein: The coated lithium-rich metal oxide material is the coated lithium-rich metal oxide material according to any one of claims 1 to 9.
13. The method according to any one of claims 10 to 12, wherein The operating parameters of the plasma enhanced chemical vapor deposition include: The microwave power is 200-1000W, optionally 200-800W or 500-1000W; and / or, The gas pressure in the chemical vapor deposition furnace is -10 to 1000 Pa, which can be 10 to 1000 Pa or -10 to 100 Pa; and / or, The temperature inside the chemical vapor deposition furnace is 400° C. to 600° C., optionally 450° C. to 550° C.; and / or, The deposition time is 2 to 10 hours, optionally 4 to 8 hours, more optionally 5 to 8 hours; and / or, The gas flow rate of the gas inlet of the chemical vapor deposition furnace is 10 to 1000 sccm, optionally 100 to 700 sccm, and more optionally 200 to 500 sccm.
14. The method according to any one of claims 10 to 13, wherein The raw materials used in the coating treatment are selected from one or more of a carbon source, a silicon oxide source, and a metal oxide source; Optionally, the raw materials used for the coating treatment are selected from one or more of an organic carbon source, an organic silicon source, an inorganic silicon source, an organic aluminum source, an inorganic aluminum source, an organic titanium source and an inorganic titanium source; Optionally, the raw materials used for the coating treatment are selected from one or more of ethylene, acetylene, methane, acetone, ethanol, benzene, tetraethyl orthosilicate, silicon tetrachloride, aluminum isopropoxide, tetrabutyl titanate and titanium tetrachloride, and more optionally selected from one or more of ethylene, acetylene, methane, tetraethyl orthosilicate, aluminum isopropoxide and tetrabutyl titanate.
15. The method according to any one of claims 10 to 14, wherein The sintering temperature is 500° C. to 700° C., optionally 550° C. to 650° C., more preferably 600° C. to 650° C.; and / or, The sintering time is 4 hours to 10 hours, optionally 6 hours to 8 hours, more optionally 6 hours to 7 hours; and / or, The heating rate of the sintering is 2°C / min to 8°C / min, and can be optionally 4°C / min to 6°C / min; and / or, The sintering is performed in an inert atmosphere.
16. The method according to any one of claims 10 to 15, wherein The lithium element in the lithium source and the Li z MO y’ The molar ratio is (az):
1.
17. The method according to any one of claims 10 to 16, wherein Before the coating treatment, the Li z MO y’ broken; and / or, Before the coating process, the raw materials used in the coating process are gasified, and optionally the raw materials used in the coating process are gasified at 300° C. to 500° C.; and / or, The prepared coated lithium-rich metal oxide material is crushed and sieved, optionally in a dry environment.
18. The method according to any one of claims 10 to 17, wherein The Li z MO y’ Prepared by the following steps: A lithium source and a source of element M are mixed and sintered; wherein the molar ratio of the lithium element in the lithium source to the element M in the source of element M is 0.98:1 to 1.09:1, optionally 0.98:1 to 1.02:1 or 1:1 to 1.09:1, and more optionally 1:1 to 1.05:
1.
19. The method according to claim 18, wherein Preparation of the Li z MO y’ In the steps: The sintering temperature is 400° C. to 600° C., and can be optionally 450° C. to 550° C.; and / or, The sintering time is 2 hours to 8 hours, and can be 4 hours to 6 hours; and / or, The heating rate of the sintering is 4°C / min to 10°C / min, and can be 6°C / min to 8°C / min; and / or, The sintering is performed in an inert atmosphere.
20. The method according to claim 18 or 19, wherein The lithium source includes one or more of lithium oxide, lithium carbonate, lithium oxalate, lithium acetate and lithium hydroxide; and / or, The source of the M element is selected from one or more of the oxide, hydroxide, halide, sulfate, carbonate, nitrate, oxalate, acetate, sulfide and nitride of the M element, and can be the oxide of the M element.
21. A method for measuring a coating layer in a coated lithium-rich metal oxide material, comprising the following steps: Provided is a coated lithium-rich metal oxide material, comprising a core and a coating layer covering the core, wherein the core comprises Li a MO y ;in, The M comprises one or more elements selected from the group consisting of Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, and Cr, 2≤a≤6, 2≤y≤4; and the coating layer comprises one or more elements selected from the group consisting of carbon, silicon oxide, and metal oxide. The coated lithium-rich metal oxide material and the solvent are mixed in a mass ratio of 1:50 to 1:1, and optionally in a mass ratio of 1:50 to 1:10, wherein the solvent consists of water and ethanol, the mass content of the water in the solvent is b, and b satisfies: when 2≤a<3, b=100%-a×10%; when 3≤a<4, b=100%-a×20%; when 4≤a≤6, b=0; The liquid phase in the obtained mixture is separated and titrated to calculate the free lithium content d dissolved in the coated lithium-rich metal oxide material to confirm whether the d value satisfies: When 2≤a<3, d≤500ppm; when 3≤a<4, d≤1000ppm; when 4≤a≤6, d≤1500ppm.
22. The coated lithium-rich metal oxide material according to claim 2 or the method according to claim 21, wherein: The mixing time is 1 min to 4 min, optionally 1 min to 3 min; and / or, The mixing is carried out under stirring conditions of 200 rpm to 800 rpm, and can be carried out under stirring conditions of 400 rpm to 800 rpm; and / or, The assay is performed at 25°C; and / or, The titration is a potentiometric titration.
23. The coated lithium-rich metal oxide material according to claim 2 or the method according to claim 21, wherein: The free lithium content dissolved in the coated lithium-rich metal oxide material is determined by the following steps: The coated lithium-rich metal oxide material and the solvent are mixed in a mass ratio of 1:50 to 1:1, and optionally in a mass ratio of 1:50 to 1:10, wherein the solvent consists of water and ethanol, the mass content of the water in the solvent is b, and b satisfies: when 2≤a<3, b=100%-a×10%; when 3≤a<4, b=100%-a×20%; when 4≤a≤6, b=0; Separate the liquid phase from the resulting mixture, take the liquid phase, and perform potentiometric titration using an ethanol solution of hydrochloric acid as the titrant. The titrant consumption volumes corresponding to the two potential jump points during the titration are V1 mL and V2 mL, respectively, and V2>V1. The free lithium content d value dissolved in the coated lithium-rich metal oxide material is calculated according to the following formula: d=C×V a ×(69.4684V2-0.0424V1) / (m×V b ) in, m represents the mass of the coated lithium-rich metal oxide material, in g; V a Indicates the volume of the solvent in mL; V b Indicates the volume of the liquid phase taken, in mL; C represents the concentration of hydrochloric acid in the titrant, in mol / L.
24. A positive electrode plate, comprising the coated lithium-rich metal oxide material according to any one of claims 1 to 9 or any one of claims 22 to 23, or the coated lithium-rich metal oxide material prepared by the method according to any one of claims 10 to 20.
25. A battery comprising the coated lithium-rich metal oxide material according to any one of claims 1 to 9 or any one of claims 22 to 23, the coated lithium-rich metal oxide material prepared by the method according to any one of claims 10 to 20, or the positive electrode sheet according to claim 24.
26. An electrical device comprising the battery according to claim 25.
Citation Information
Patent Citations
Carbon-coated lithium-rich oxide composite material and preparation method thereof
CN111725576A
Lithium molybdate coated lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN113078316A
Positive lithium supplement additive, positive pole piece, preparation method of positive pole piece and lithium ion battery
CN114079086A
Lithium-rich oxide with core-shell structure as well as preparation method and application of lithium-rich oxide
CN115172700A
Positive electrode lithium supplement additive and preparation method and application thereof
CN115215376A
